Investigation of an N‐Terminal Prohormone of Brain Natriuretic Peptide Point‐of‐Care ELISA in Clinically Normal Cats and Cats With Cardiac Disease. (15th June 2017) - Harris, A.N.; Beatty, S.S.; Estrada, A.H.; Winter, B.; Bohannon, M.; Sosa, I.; Hanscom, J.; Mainville, C.A.; Gallagher, A.E.
Abstract : Background: N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP) concentrations may be increased in cats with various cardiac disorders. The point‐of‐care (POC) ELISA assay uses the same biologic reagents as the quantitative NT‐proBNP ELISA. Previous studies have evaluated the sensitivity and specificity of the POC ELISA in cats with cardiac disease. Objectives: To prospectively evaluate the diagnostic utility of the POC ELISA in a select population of cats. Animals: Thirty‐eight client‐owned cats presented to the University of Florida Cardiology Service for cardiac evaluation. Fifteen apparently healthy cats recruited as part of another study. Methods: Physical examination and echocardiography were performed in all cats. The POC ELISA was assessed visually as either positive or negative by a reader blinded to the echocardiographic findings, and results were analyzed relative to quantitative assay results. Results: Twenty‐six cats were diagnosed with underlying cardiac disease, and 27 cats were considered free of cardiac disease. Cats with cardiac disease included: 21 with hypertrophic cardiomyopathy, 2 with unclassified cardiomyopathy, 2 with restrictive cardiomyopathy, and 1 with 3rd degree atrioventricular (AV) block. The POC ELISA differentiated cats with cardiac disease with a sensitivity of 65.4% and specificity of 100%. Conclusions and Clinical Importance: The POC NT‐proBNP ELISA performed moderately well in a selected population of cats. A negative test result cannot exclude the presence of underlying cardiac disease, and a positive test result indicates that cardiac disease likely is present, but further diagnostic investigation would be indicated for a definitive diagnosis.